Investigation on method of reducing surface leakage current of the CdZnTe photoconductive detector with MSM structure. (January 2022) - Feng, Chengjie; Min, Jiahua; Liang, Xiaoyan; Zhang, Jijun; Wang, Linjun; Shen, Yue
Abstract: The surface leakage current (SLC) of CdZnTe is an important factor affecting detection performance. In this work, we established a two-dimensional model of metal-semiconductor-metal (MSM) structured CdZnTe with a low-resistance layer on the surface. The composition of SLC and the distribution of the internal electric field are analyzed by simulation. The study found that the change of electrode size will change the contribution of SLC from cathode, anode and side surfaces. With the increase of electrode size, the contribution of SLC to total leakage current decreases gradually, and the internal electric field distribution becomes more uniform. According to the conclusions of simulation, we have proposed a simple and accurate method to estimate the bulk resistivity and SLC of CdZnTe. In addition, combined with a series of experiments, we have also summarized several methods which can reduce the contribution of the SLC in MSM structured CdZnTe detector in order to improve energy resolution.